DIMENSI BIG FIVE PERSONALITY DAN PSYCHOLOGICAL WELL-BEING MAHASISWA RANTAU ASAL DAERAH 3T - Sicilia Tandi Bua; Arthur Huwae (Journal of Psychology and Instruction, 2023)
Indonesia has 62 territory of the frontier, Outermost, and lagging (3T) where the area is located far from urban areas and scattered throughout the territory of Indonesia. It makes students have to go, where regional students described as someone who continue their education in other areas, which is caused by uneven system of higher education. As a student overseas, certainly many of the challenges faced by the start of differences in language and culture, so the importance of forming a good personality in achieving psychological well-being. Therefore, this study aims to determine the contribution of dimensions of big five personality on psychological well-being of regional students derived from 3T. The method used is quantitative with the design of the simple regression. Participants in this study were 53 regional students derived from the 3T in Satya Wacana Christian University with a snowball sampling technique. The measurement of research using the scale of big five personality and the scale of psychological well-being. Based on the results of the t test obtained the dimensions of extraversion, openness to experience and conscientiousness of the variables of the big five personality has an influence on psychological well-being, with a significance less than 0.05. While on the dimensions of neuroticism and agreeableness have no contribution to psychological well-being